Romanticism, lyricism, and history - Zimmerman, Sarah MacKenzie (State University of New York Press, 1999)
"Arguing against a persistent view of Romantic lyricism as an inherently introspective mode, this book examines how Charlotte Smith, William Wordsworth, and John Clare recognized end employed the mode's immense capacity for engaging reading audiences in reflections both personal and social. Zimmerman focuses new attention on the Romantic lyric's audiences--not the silent, passive auditor of canonical paradigms, but historical readers and critics who can tell us more than we have asked about the mode's rhetorical possibilities. She situates poems within the specific circumstances of their production and consumption, including the aftermath in England of the French Revolution, rural poverty, the processes of parliamentary enclosure, the biographical contours of poet's careers, and the myriad exchanges among poets, patrons, publishers, critics, and readers in the literary marketplace. Book jacket."--Jacket